2014
DOI: 10.3109/10717544.2013.871373
|View full text |Cite
|
Sign up to set email alerts
|

Improving transfection efficiency of ultrapure oligochitosan/DNA polyplexes by medium acidification

Abstract: Context: Ultrapure oligochitosans (UOCs) have recently been reported as efficient nonviral vectors for corneal and retinal gene delivery. However, the influence of some physicochemical factors on the transfection efficiency, such as the pH, remains unclear. Deeper in vitro research of these factors could provide valuable information for future clinical applications. Objective: The aim of this study is to determine the influence of the pH decrease on the transfection efficiency of UOC/pDNA polyplexes in HEK293 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Also, cellular uptake is one of the major obstacles for a successful gene delivery strategy and polyplexes are thought to enter the cell via endocytosis in a process that may be dependent on polyplex charge [26]. A higher surface charge can facilitate electrostatic interactions with the negatively charged proteoglycans in cellular membranes and hence promote polyplex internalization [27]. Our results show a positive correlation between polyplex surface charge and transfection efficiency that is in agreement with the literature.…”
Section: Transfection Efficiency Is Formulation-dependentsupporting
confidence: 82%
“…Also, cellular uptake is one of the major obstacles for a successful gene delivery strategy and polyplexes are thought to enter the cell via endocytosis in a process that may be dependent on polyplex charge [26]. A higher surface charge can facilitate electrostatic interactions with the negatively charged proteoglycans in cellular membranes and hence promote polyplex internalization [27]. Our results show a positive correlation between polyplex surface charge and transfection efficiency that is in agreement with the literature.…”
Section: Transfection Efficiency Is Formulation-dependentsupporting
confidence: 82%
“…Koping-Hoggard et al observed a size increase from 68 to 174 nm when chitosan Mw increased from 2 to 7 kDa for polyplexes prepared at N/P ratio of 60 [22]. Our research group has recently described that particle size of HMWC is around 4-hold higher than the size of polyplexes based on LMWC (5.3 kDa; 7kDa), prepared at N/P of 20 [30]. However, other authors have reported a decrease in size of polyplexes with increased Ch M w [19].…”
Section: Physico-chemical Characterization Of Lmwc-pdna Polyplexesmentioning
confidence: 99%
“…According to Lavertu and colleagues the best mixing technique was found to be adding Ch over pDNA, pippeting up and down and tapping the tube gently [26]. Other authors, however, have reported that for the correct formation of LMWC-pDNA polyplexes a more vigorous vortex agitation is preferred [27][28][29][30]. The incubation time required for the correct formation of the polyplexes is another factor to consider.…”
Section: Lmwc-pdna Polyplexes Formation Processmentioning
confidence: 99%
See 2 more Smart Citations